A Novel Benzenesulfonylurea-Substituted Pyridazinone Derivative with Antidiabetic Effect as the Peroxisome Proliferator-activated Receptor (PPAR-γ) Agonist - Fatisa, Yuni; Yasthophi, Arif; Elviyenti, Elviyenti; Ikhtiaruddin, Ihsan; Frimayanti, Neni; Teruna, Hilwan Yuda; Jasril, Jasril (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2025)
Peroxisome Proliferator-activated Receptor (PPAR-γ) protein is one of the target proteins for insulin sensitivity therapy in Type 2 DM. PPAR-γ has a key role as a nuclear receptor that regulates the expression of several metabolism-related genes. This research aims to synthesize a novel benzenesulfonylurea-substituted pyridazinone derivative, namely (E)-N'-(1-(4-(3-(4-methoxyphenyl)-6-oxopyridazin-1(6H)- yl)phenyl)ethylidene)-4-methylbenzenesulfonohydrazide (8) and predicted it activity as the PPAR-γ agonist using a molecular docking approach and ADMET profiles. The compound 8 was obtained through a Schiff base condensation reaction between compound 6, p-tosyl hydrazine, and a glacial acetic acid catalyst using monowave. The purity of the compound was determined by TLC test, and melting point measurement. The structure was confirmed through FTIR, 1H-NMR, C-NMR and HRMS analysis. Molecular docking studies were carried out on the crystal structure of the human PPAR-γ Ligand Binding Domain target protein in complex with the α-aryloxyphenyl acetic acid agonist (PDB ID 1ZEO). The results of the docking show that compound 8 has a lower binding free energy than rosiglitazone (positive control) with a free energy value (S score) = -13.513 kcal/mol and -8.3089 kcal/mol, respectively. Compound 8 can form two hydrogen bonds with residues His323 and Ser289, π-π interactions with Phe363 and π-H interactions with Cys285. The interactions are similar to the interaction between the native ligand agonists α-aryloxyphenyl acetic acid and rosiglitazone with the target protein. Furthermore, compound 8 is predicted to have a moderate ADME profile. The results support that compound 8 can be developed as a PPAR-γ agonist candidate for the antidiabetic therapeutic agent.